Effect of Wastewater on Heavy Metal Accumulation in Cystoseria sp. (Brown algae) and Enteromorpha. sp. (Green algae) in Derna Coast, Libya - Zatout, Masoud.M.M.; Abdalhafid, Yousef K. A.; Alhage, Salmeen. H. (Al-Mukhtar Journal of Sciences, 2018)
In this work was studied effect of wastewater pollution on heavy metal accumulation in Cystoseria sp., (brown seaweed) and Enteromorpha sp. (Green algae), in an effort to gain some insight into the level of metal contamination which might exist in the coastal marine environment along the Derna coast. Assessed by measuring the concentration of heavy metals as Pb, Zn, Mn and Cd, in the algae tissue and seawater. The results indicate concentrations of metals were invariably slightly higher in Enteromorpha sp., than in Cystoseria sp., at all sampling stations. The metals concentrations recorded for the different tissues and sites of the present study confirm the higher concentrations usually observed in summer. The average MPI was highest (0.86) for the both species inhabiting S6 station and least (0.29) at S1 station. In general, the all of heavy metals show no detrimental effects on the domestic aquatic environment of Derna coast. However, must be monitored continuously to ensure that they stay at harmless levels.